Expansion of the Criminal Law and control of migratory flows in the contemporary world - de Aguiar, Jeannine Tonetto; Wermuth, Maiquel Ângelo Dezordi (Revista Jurídica Portucalense, 2018)
The expansion of Criminal Law in the contemporary society, resulting from its consideration as preciput instrument of social control in the face of the risks that this society presents, does not match the characteristic Punitive Law model of Democratic States of Law. This expansion stems from the diffusion of social discourse of fear and insecurity that are widely leveraged and manifested by the media and, where appropriate by politics, produce measures advocating selective segregation of groups considered as "producers" of risk, such as immigrants undocumented invariably related to increased crime and insecurity in the countries of destination. These measures represent the institutionalization of a state of exception for dealing with issues related to migration policies in countries where this phenomenon is more intense, as is the case of some central European Union countries, which have been converting the otherness of irregular immigrants in principle of risk, establishing thus a etiquetamendo (not citizens) of those individuals, recommending the use of a new penalty (Criminal Law of the author) that by criminalizing them, puts them in an extremely vulnerable situation. In this sense, this study seeks to analyze the institutionalization of this new Criminal Law model, based on exclusionary, repressive and segregationist measures which fall the actual realization of human rights, to confront the fundamental rights and guarantees of undocumented migrants, to transform them into mere "objects" of punishment.